Size Distribution and Gonad Development of Female Green Press (Macrobrachium sp) in Togafo Village, West Ternate Di Sitrict Ternate City - Muin, Nova; Serosero, Rugaya H.; Abubakar, Yuyun; Widiyanti, Sri Endah; Sunarti, Sunarti; Rina, Rina (Jurnal Biologi Tropis, 2024)
ln Togafo Village, West Ternate  District, is one of  the natural habitats for giant prawns (Macrobrachium Sp). However, in that area there are frequent catching which are not environmentally friendly by using potash so that the habitat is very disturbed by its development, even though the marpu produce giant prawns naturally well, this can be seen in the activity during fishing that too k place in Togafo Village river. The aim of this research was to determine the size distrubution and gonadal development of giant prawns prawns (Macrobrachium Sp). Sampling is done by hand and using a filter cach. Catching with hands is done by draining the water so that the shrimp can come out and to make it easier to catch. The 2 inch mesh size  filter fishing gear as a fishing aid was spread over tha water flow in Togafo Village at 2 stations. Stasion 1 is the middile of the in Togafo Waterway (border of Ave Taduma). And station 2 is in the middle of the water flow (the people’s plantation). The arrests were carried out for three months . Size distribution of the combined total length of giant prawn catches at station 1 and 2 in november ranfers from 4,4 -9,0 cm and weight rangers from 5-10 grams, in March the total length is 3,5- 8,4 cm and weight April 1-9 grams and the total  length rangers from 5,6 – 9,9 cm weighing 1-5g. Perken prawns that mature gonads at station 1 and  in November are III and IV, in March are III and April are III.